Evaluation of geometry skills: Integrating logic and drawing indicators through GeoGebra-based learning - Hamidah, Hamidah; Kusuma, Jaka Wijaya; Chotimah, Siti; Senjayawati, Eka (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
The problem in this study is to evaluate the improvement of students' geometry skills using the GeoGebra application by focusing on two key indicators: logical thinking and drawing skills. This study employs both quantitative and qualitative methods. In the first stage, quantitative data were collected through pretests and posttests to measure student geometry skill changes. In the second stage, qualitative methods were used to explore and validate the quantitative findings through geometry skill tasks and interviews. The research subjects were second-semester mathematics education students at Bina Bangsa University, selected using purposive sampling. The findings reveal that students who engaged in geometry learning with GeoGebra experienced significant improvement in both logical reasoning and geometric drawing skills. Students became better at visualizing geometric problems, constructing geometric figures accurately, and connecting visual information to logical reasoning processes. GeoGebra improved students’ ability to identify patterns, perform deductions, draw conclusions, and visually communicate geometric ideas. It is recommended that GeoGebra be complemented with mathematical writing and drawing activities in geometry instruction to strengthen further the logical and visual dimensions of students’ geometric thinking.